Effect of Foot Reflection Massage on Blood Pressure Reduction in Hypertension Patients - Sri Suryaningsih; Rian Tasalim; Subhannur Rahman (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
Hypertension is a chronic condition caused by an increase in blood pressure above normal limits. Many non-pharmacological treatments have been found to lower blood pressure, such as foot reflexology, which has a relaxing effect to improve blood circulation. Objective: To analyze the effect of foot reflexology on reducing blood pressure in hypertensive patients. Methods: foot reflexology is given which has 3 stages of administration where each treatment is given for 15-20 minutes. This research is a pre-experimental research with an approach using the One Group Pretest Posttest Design. The population in this study were hypertension sufferers in the village of Paku Alam RT 02. In taking the sample the researchers used the purposive sampling technique with a total of 15 respondents and performed foot reflexology massage. The analysis used Paired t-test. Results: the results showed that blood pressure decreased after giving foot reflexology. After processing, based on the paired t-test, p value <0.005 (0.00<0.05) was obtained, so H0 was rejected and Ha was accepted. Conclusion: The Effect of Foot Reflexology Massage on Blood Pressure Reduction in Hypertension Patients in Paku Alam Village.